Bilateral muscular axillary arch: An anatomic study and clinical considerations - Chunder, R; Guha, R (Journal of College of Medical Sciences-Nepal, 2015)
The axillary arch is a variative muscular slip encountered in the axillary region which usually connects latissimus dorsi to pectoralis major. Reported here is a rare case of bilateral axillary arch splitting the radial nerve into two roots in each side as observed during routine dissection of the axillary region of an old male cadaver. The anatomy, surgical implications, and embryology of the anomalous muscle have been discussed. Clinicians should be aware of its existence as it can give rise to different pathologies. It should be recognised and excised to expose the axillary artery and vein in patients with trauma and to perform axillary lymphadenectomy or axillary bypass. It should be considered in the differential diagnosis of axillary masses or in a history of intermittent axillary vein obstruction. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 56-60